2017
DOI: 10.4012/dmj.2016-135
|View full text |Cite
|
Sign up to set email alerts
|

SiO<sub>2</sub>-nanocomposite film coating of CAD/CAM composite resin blocks improves surface hardness and reduces susceptibility to bacterial adhesion

Abstract: Composite resin blocks for computer-aided design/computer-aided manufacturing (CAD/CAM) applications have recently become available. However, CAD/CAM composite resins have lower wear resistance and accumulate more plaque than CAD/CAM ceramic materials. We assessed the effects of SiO2-nanocomposite film coating of four types of CAD/CAM composite resin blocks: Cerasmart, Katana Avencia block, Lava Ultimate, and Block HC on surface hardness and bacterial attachment. All composite blocks with coating demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…e obtained result was slightly lower compared to the manufacturer's data [16] (140.43 vs. 154.6) and higher compared to the data obtained by Alamoush et al [15], (140.43 vs. 121.8). Similarly, CS microhardness was higher compared to Lauvahutaton et al [20], Lawson et al [32], and Kamonwanon et al [46]. Microhardness values for HC were higher than the value contained in the independent data and that of the manufacturer's [20,46].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…e obtained result was slightly lower compared to the manufacturer's data [16] (140.43 vs. 154.6) and higher compared to the data obtained by Alamoush et al [15], (140.43 vs. 121.8). Similarly, CS microhardness was higher compared to Lauvahutaton et al [20], Lawson et al [32], and Kamonwanon et al [46]. Microhardness values for HC were higher than the value contained in the independent data and that of the manufacturer's [20,46].…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, CS microhardness was higher compared to Lauvahutaton et al [20], Lawson et al [32], and Kamonwanon et al [46]. Microhardness values for HC were higher than the value contained in the independent data and that of the manufacturer's [20,46]. Kamonwanon et al [46] found lower hardness value (almost half) for CS, AV, and HC than our results and also lower than those obtained by Alamoush et al [15], Lauvahutaton et al [20], and Lawson et al [32].…”
Section: Discussionmentioning
confidence: 78%
“…Up-to-date, CAD/CAM composite materials are mostly available for subtractive fabrication procedures with a CAD/CAM milling machine in the form of industrially homogenously fabricated blocks. These blocks have been shown to have superior characteristics compared to direct composite materials [4,5]. These materials are used for permanent single restorations.…”
Section: Introductionmentioning
confidence: 99%
“…Ceramics also age better and have a lower plaque retention than modified PEEK material, so slight color difference between the endocrown restoration and tooth especially with the extended examination period, all cases of lithium disilicate and translucent zirconia rated alpha or Bravo along the complete examination period but the modified PEEK also except the at 36 months period rated charlie and this score also recorded for the surface texture criteria and this may be due to roughening the surface and other factors as inherent discoloration of resinous, improper oral hygiene, smoking especially male cases and drinks. 40 In our study, the surface texture of the restorations rated with alpha and Bravo for the all the tested materials during the 36 months follow up periods but the rate of Bravo steadily increased with time with exception at 36 months the modified PEEK endocrown recorded charlie rate. There are numerous reasons that can influence the surface texture like tooth cleaning, abrasion, or attrition [42,43] .…”
Section: Discussionmentioning
confidence: 53%
“…Based on ,the finding of this study synchronized with this interpretation, whereas the success of lithium disilicate endocrowns was 100% along the 36 months examination period related to bonding but one case fractured may be due high masticatory force or uniaxial force especially the high force at the first molar area, but modified peek endocrowns was 100% between alpha and Bravo rating 30 months but after that number of cases rated Charlie more than the other cases, however the satisfaction of patients rated charlie in 4 cases and these cases repaired to the successor criteria. Collectively the lithium disilicate the best because they have the highest score of alpha rate and Bravo rate more than zirconia and PEEK cases 40 .…”
Section: Discussionmentioning
confidence: 99%